From Brothers War to Border War. Conduct of an Interstate War in the Post-Cold War Era: Ethiopia-Eritrea (1998-2000) - Dias, Alexandra Magnólia (2016)
Interstate wars are not one of the most salient features of current World Politics. Indeed, the prevailing patterns of contemporary armed conflict show an increasing trend in intrastate wars that spill over borders. The paper aims to provide insights from an interstate war in the post-Cold War era to the debate on the transformation of warfare (Old vs. New Wars and their conduct). Beyond the continuities with the 30 years civil war, namely in the relations between the two former insurgent movements, the Tigray People's Liberation Front(TPLF) and the Eritrean People's Liberation Front (EPLF), the 1998-2000 war was waged between the armed forces of two sovereign states. This is one of the few cases of interstate war in Africa.The case-study provides evidence to contradict the strand of the literature which claims that we are witnessing a decisive transformation of warfare (Van Creveld 1991);(Kaldor 1999).The central claim of this paper is that neighboring states fight over territory. The conduct of the war allows understanding under which circumstances is territory significant. The paper will start with a brief synopsis of the conflict followed by an analysis of the conduct of the war. A map of the contested areas and a timeline of recent developments from 5 October 2005 up to December 2005 are annexed.The analysis of the conduct of the war confirms the centrality of territory to understand how the war unfolded and ended. As the war unfolded Badme was transformed from a barren strip of land into an emblem and symbol of statehood. Indeed, territory is central to understanding not only the conduct, but also the causes and the outcomes of the 1998-2000 interstate war. However, in the scope of this paper the main focus remains the conduct of the war. The May 2005 Elections in Ethiopia and recent developments, since October 2005, remind the significance of gathering data on the Final Round of Fighting ( May-June 2000) and more specifically on the way the war was brought to an end ( June 2000 Cease-fire). Finally, the conduct of the war shows that this classical 'Old War', in the post-Cold War era, displays characteristics highlighted in the 'New Wars' literature.